Effect of modified Aloe vera L gel in the treatment of liver toxicity and induced alopecia with CCl4 and DMSO in mice - Saavedra, Félix (2013)
The purpose of this study was to assess whether the loss of fur and changes in liver enzymes, aspartate aminotransferase (AST) and alanine aminotransferase (ALT), produced in albino mice by oral administration of carbon tetrachloride and dimethyl sulfoxide (DMSO) (1:1), 2 mL/kg dose, are reversible processes when administered modified aloe gel (GSM) orally daily dose of 8 mL/kg of weight. Tests carried out at 13, 18 and 33 days from starting treatment with GSM, was evidenced significant and progressive decrease in AST and ALT without significant variations in proteins and phosphatases; whereas triglyceride level by the effect of GSM (group B), experienced significant decrease during the first week compared to mice given CCl4+DMSO mixture (group A), specimens that also recovered the fur on its chest and muzzle at 33 days of starting the experiment. The mice in the groups: control, GSM, DMSO+feed and water+feed, did not present significant variation in the studied indicators.